Plug&Play Places Lifeworlds of Multilocal Creative Knowledge Workers - Nadler, Robert (De Gruyter, 2014)
Plug&Play Places brings forth the idea that places have to be understood as individual items, which are configured and then plugged into the 'system' of the own lifeworld. They can be 'played' without great effort once an individual needs to make use of them. This new type of place attachment is a form of subjective standardization of place, which complements the well-known models of objective standardization of places
Description based on publisher supplied metadata and other sources
Keywords: Gesellschaft; Arts -- Economic aspects; Creative ability -- Economic aspects; Cultural industries -- Economic aspects; Cultural industries -- Employees; Cultural industries -- Social aspects; Transnationalism; Arbeitsmobilität; Kulturwirtschaft; Hochschulschrift